Faktor – Faktor yang Menentukan Financial Distress pada Perusahaan di Industri Manufaktur yang Terdaftar di BEI Tahun 2020 - 2022 - Margareta Dwi Saputri; Bambang Sudiyatno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study tested the impact of profitability ratio, liquidity ratio and leverage ratio on financial distress in manufacturing companies listed on the Indonesian Stock Exchange. In this study samples were taken from manufacturing companies listed on the Indonesian Stock Exchange in the period 2020 – 2022 using purposive sampling method. Relationships or influences of variables are described using double regression analysis methods. The results of the research show that profitability has a positive and significant effect on financial distress. This suggests that when profitability increases, then financial distresses will also increase. The activity and size of the company have no significant influence on the financial distress. In this study the most dominant contributing variable is the activity measured by the total asset turnover.